Pacific pearls proliferate - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Over the last six years, there have been concerted efforts to adapt the culturing of the black pearl oyster to conditions in the western Pacific. In 1999, the Cook Islands pearl farms earned US$ 5 million. Currently the Solomon, Fiji and Marshall...